Long non-coding RNA NEAT1 promotes steatosis via enhancement of estrogen receptor alpha-mediated AQP7 expression in HepG2 cells - Xiaohua Fu; Jing Zhu; Lin Zhang; Jing Shu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Hepatic steatosis is one of the most important features of the pathogenesis for non-alcoholic fatty liver disease. Fat deposition in liver cells can influence hepatic lipogenesis along with other metabolic pathways and further lead to the irreversible liver cirrhosis and injury. However, the underlying mechanism of steatosis remains largely unexplored. Our previous study revealed that AQP7 played an important role in liver steatosis. In this study, we determined that the transcriptional level of AQP7 was up-regulated by estrogen receptor alpha (ERα) upon 17β-estradiol (E2) and oleic acids treated HepG2 cells. Furthermore, we identified long non-coding RNA nuclear enriched abundant transcript 1 (NEAT1) as a potential hallmark which was down-regulated in ERα silencing HepG2 cells by RNA-Seq. Finally, we validated that the 3’ terminal nucleotides of NEAT1 were contributed for the interaction with ERα to facilitate AQP7 transcription to suppress liver steatosis. Overall, our study gave evidence that NEAT1 played an important role in the activation of ERα to regulate AQP7-mediated hepatic steatosis.